Natriuretic Peptide System Activation in Acute Heart Failure Patients with Diabetes - Filipe M. Cunha; Joana Pereira; Pedro Marques; Helena Moreira; Pedro Rodrigues; Maria João Pinto; Patrícia Lourenço; Paulo Bettencourt (Journal of Diabetes Research)
Background. Elevated B-type natriuretic peptide (BNP) is a hallmark in heart failure (HF). Diabetic patients with chronic HF seem to have higher BNP than nondiabetics. We studied, in acute HF, if BNP levels are different between diabetics and nondiabetics. Methods. From a prospectively recruited population of acute HF patients, we selected a convenience sample. In pair-matched analysis, each diabetic patient was matched with a nondiabetic of the same age (±1 year), gender, and according to left ventricular systolic dysfunction. Diabetics and nondiabetics were compared. Cox-regression analysis was used to analyse the prognostic impact of diabetes. Results. We studied 328 patients, mean age: 78 years, 44.5% male. Diabetics were more often hypertensive and had ischemic HF; they had higher body mass index, lower haemoglobin, and worse renal function. Diabetics were more often discharged on ACE inhibitors/ARB, antiplatelet therapy, and statins. Neither admission nor discharge BNP values differed between diabetics and pair-matched nondiabetics. One-year mortality was also nondifferent between pairs of diabetics and nondiabetics: 44 (26.8%) and 46 (28.0%), respectively. HR for 1-year mortality in diabetics was 1.00 (95% CI: 0.82–1.24) compared with nondiabetics. Conclusions. HF patients with diabetes have similar neurohumoral activation when compared with nondiabetics. One-year mortality is also nondifferent after matching for age, gender, and systolic function.